Acetyl-l-carnitineamelioratesmitochondrial damage and apoptosis following spinal cord injury in rats. (14th September 2015) - Zhang, Zhen-yu; Fan, Zhong-kai; Cao, Yang; Jia, Zhi-qiang; Li, Gang; Zhi, Xiao-dong; Yu, De-shui; Lv, Gang
Highlights: ALC prevented ultrastructural changes of mitochondria after SCI. ALC improved dynamic alternations of mitochondria after SCI. ALC suppressed cell apoptosis following SCI. Abstract: Acetyl-l -carnitine (ALC) facilitates the entry and exit of fatty acids from mitochondria and plays an essential role in energy metabolism. Although ALC is known to exert neuroprotective effects in multiple neurological diseases, its effects on spinal cord injury (SCI)-induced mitochondrial impairments and apoptosis remain unclear. In this study, we aimed to evaluate the putative effects of ALC on mitochondrial dysfunction and apoptosis induced by SCI in a rodent model. Our results indicate that SCI elicits dynamic alternations in the expression of mitochondria-related proteins. Transmission electron microscopy analysis showed that ALC administration abrogated key ultrastructural abnormalities in mitochondria at 24 h after SCI by maintaining mitochondrial length, reducing the number of damaged mitochondria, and reversing mitochondrial score ( P  < 0.05 compared with SCI group). In addition, ALC administration maintained the mitochondrial membrane potential and mitochondrial Na + -K + -ATPase activity following SCI ( P  < 0.05 compared with SCI group). ALC administration reversed the downregulation of mitofusin 1 (Mfn1), Mfn2, Bcl-2, and the upregulation of dynamin-related protein 1 (Drp1), mitochondrial fission 1 (Fis1), Bcl-2-associated X protein (Bax) and cytosol cytochrome c (cyto-CytC) induced by SCI ( P  < 0.05 compared with SCI group). Finally ALC administration greatly reduced the percentage of apoptotic cells compared with the SCI group ( P  < 0.01 ). In conclusion, our findings demonstrated that ALC ameliorated SCI-induced mitochondrial structural alternations, mitochondrial dysfunction, and apoptosis.